The effect of posture on muscle endurance, fatigue and blood flow - Egaña Etxeberria, Mikel (Trinity College (Dublin, Ireland). Department of Physiology, 2005)
Tilting the body from the supine to an upright position increases the time on a maximal graded cycle test by -1 5 % . However, this effect during constant-load cycling is unknown, and in addition, it is also unknown if this postural effect is observed during exercise involving isolated muscle groups. Therefore, we tested the effect of upright versus supine posture on endurance during graded and high-intensity constant-load cycling exercise (Chapter 2) and on the strength, endurance, fatigue (Chapters 3 and 4) and blood flow (Chapter 5) during graded and high-intensity constant-load isometric plantar flexion exercise.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin